Lifestyle Issues in Children and Adolescents with Chronic Inflammatory Bowel Diseases. (1st November 1990) - Sherman, P; Griffiths, A; Marcon, M; Smith, C; Geist, R
Abstract : The goals of therapy in chronic inflammatory bowel diseases in pediatrics include decreasing mucosa! inflammation, the restoration of optimal growth and pubertal development, and the return to a normal, age-appropriate lifestyle. The latter is best served by minimizing restrictions; for example, school attendance, extracurricular activities, travel and the child's interactions with both siblings and peers. In most instances dietary restrictions are also inappropriate and may prove detrimental. Children and adolescents are not simply 'little adults'. Teenagers dread being perceived as different from their peers. They are especially bothered therefore by cosmetic side effects associated with corticosteroid therapy and by impaired growth and pubertal development. Although not discussed openly, many adolescents are also concerned about their subsequent ability to have children and the potential for future development of neoplasms. The great majority of affected children adapt and function very well. Psychosocial factors, although clearly not the cause of inflammatory bowel diseases, are operative in many subsets of children with less than optimal function in daily activities. Children at particular risk are those with premorbid low self-esteem, dysfunction in family dynamics, or severe growth failure. Intervention and support provided through psychiatric and medical social work consultations and by the involvement of self-help groups are often key determinants for restoration of a normal lifestyle. Information about the underlying chronic disease, when provided at a level that is appropriate for age and cognitive function, can decrease anxiety and fears by reducing uncertainty and promoting a feeling of control.